Effect of Lean Green Practices on sustainability performance with mediating role of Entrepreneurship Orientation: A Resource Based View - Khan, Maryam Pervez; Talib, Noraini Abu; Kowang, Tan Owee (International Journal of Psychosocial Rehabilitation, 2020)
Sustainability performance concept has gained amplified importance in the last decades. On the other hand, with the change in market dynamics and increasing concerns for social responsibility and environment, the improvement methodologies related to the environment, operations, and society such as manufacturing practices lean and green are rising these days. However, there are minimal efforts at integrating the concepts of Lean, Green concerning sustainability performance in SMEs. As the concepts of Lean Green and their integration is necessary to balance the requirement for operational efficiency, environmental commitment and social fairness. Therefore, this study suggests a conceptual framework for the implementation of Lean, Green practices impact on the sustainability performance within business operations of Small and Medium Enterprises with mediating role of entrepreneurship orientation under the theory of Resource Based View. The proposed framework shows new pathways and paradigms for SMEs to understand the importance of Lean Green practices effect with the role of entrepreneurship orientation in their day to day performance as well as to achieve the balance between economic, social and environmental priorities.